On the Incentive and Sustainability Impact of SDGs on Innovation in Small and Medium-Sized Tourism Enterprises (SMEs) - Hermínio Alfredo (Law and Economy, 2023)
This paper investigates the influence of Sustainable Development Goals (SDGs) on innovation and sustainability in Small and Medium-sized Tourism Enterprises (SMEs) in Brazil. Through qualitative methods, including interviews and document analysis, the study explores how specific SDGs act as incentives for innovation, shaping employment strategies and responsible production processes within SMEs. The sustainability impact is evident in environmental conservation, community engagement, and responsible consumption. Despite notable achievements, challenges such as resource constraints persist, emphasizing the need for targeted support. The study concludes that aligning with SDGs positions Brazilian SMEs as contributors to global sustainability, promoting responsible and innovative business practices.